Migration from an SQL to a hybrid SQL/NoSQL data model - Sokolova, Marina V.; Gómez, Francisco J.; Borisoglebskaya, Larisa N. (Journal of management analytics, 2020)
The paper presents a redesign of a database management system for a retail business company. Initially, based on a traditional data model, it is migrated to a hybrid model which combines both SQL and NoSQL databases. This approach adds flexibility, mobility, and efficiency to the data management system. The NoSQL database uses an ontology as a data schema, which we describe in this study. The NoSQL database is consulted using the SPARQL query language, and some examples of the queries are detailed in the paper. The architecture of the system and its functionality are discussed.